Anisotropic Printed Resistor with Linear Sensitivity Based on Nano–Microfiller‐Filled Polymer Composite. (4th October 2021) - Huang, Pei; Cao, Yingze; Wei, Yawen; Cheng, Xiang; Liu, Junfeng; Zhang, Shanshan; Wang, Pengfei; Chen, Shaosong; Xia, Zhidong
Abstract: 3D printing electronics provides great potential to build structural objects with multiple functionalities, with the assistance of shape design and the shear force on the filler orientation. In the study, nano–microanisotropic sensors with oriented fillers assure its linear sensitive properties, where the sensors are 3D‐printed based upon the carbon fiber (CF)‐ and multiwalled carbon nanotube (MCNT)‐filled polydimethylsiloxane (PDMS). The synergistic effect of CF and MCNT modifies the printability, mechanical properties, and sensitivity of printed sensors. The introduction of anticatalyst and catalyst guarantee the printable mixtures with a stable printability in a long term (>15 days). Assisted by the shear flow, the fillers own the orientation ration of 78.53%, which further contribute to the linear sensing behaviors under the tensile strain of 0–20% and compressive stress of 0–20 kPa. Frequency‐domain signals and visual demonstration on the cyclic stretch test reveal that the double peak is originated from the hysteresis of the strain to applied stress. Anisotropic electromechanical behaviors of the resistors will inspire to quantitatively analyze multidimensional strains in practical applications. The fingerprint inspired resistors with multiple sensing signals further demonstrate the convenience of the printing process on the design of wearable electronics. Abstract : 3D printing electronics provides great potential to build structural objects with multiple functionalities, with the assistance of shape design and the shear force on the filler orientation. The synergy of carbon fiber‐ and multiwalled carbon nanotube‐filled anisotropic resistors is systematically prepared and studied on their printability, electromechanical behaviors, microstructure, as well as the sensing circuits design.